15 años de organismos genéticamente modificados (OGM) en Brasil: Riesgos, etiquetado y opinión pública - Biancca Scarpeline De, Castro [UNESP] (My University, 2016)
The objective of this paper is to present the introduction and diffusion of genetically modified organisms in Brazil, emphasizing the contentions about labeling and the public opinion about the issue. The findings are based on long-term research on the topic, as well as in analysis of interviews with stakeholders and the general public. It is disclose that disputes related to GMOs in Brazil were very polarized and unfolded as conflicts of risks. It is also shown that labeling is considered by those opposed to GMOs as an essential condition for the consumer´s choice of products, while companies and institutions in favor of GM products have a different opinion on the issue. The results of a survey with over than 800 Brazilian consumers indicated that they are more concerned with issues related to contamination (biological and chemical) and nutritional characteristics of foods than plant biotechnology.
15 ans d’organismes génétiquement modifiés (OGM) au Brésil: Des risques, l’étiquetage et l’opinion publique
15 anos de organismos geneticamente modificados (OGM) no Brasil: Riscos, rotulagem e opinião pública
Keywords: Consumers; Genetically modified organisms; GMO; Labeling; Public opinion; Risk